Measurement of Advertising Effectiveness in Social Networks: Current Overview and Development of a Model - Torres-Romay, Emma (Journal of Marketing Development and Competitiveness, 2022)
The rise of social networks has resulted in an increase in advertising on these media. In this paper we propose to review this reality in our country and can determine what is the current reality about the advertising effectiveness of these networks. For this, we propose a combined study that will allow us to have a general overview, giving rise to a measurement model that determines the most important concepts and parameters when assessing the effectiveness of this communicative resource.